Analysis of mineral and heavy metals in ﬁsh otoliths in theTigris River, Turkey - Muhammed Yaşar Dörtbudak; Hikmet Dinç; Serbest Bilici (Revista Científica)
Rising pollution levels pose significant threats to fisheries. By analysing the different components of fish body structures, the interactions that occur in response to environmental changes can be better understood. Otoliths are structures in the inner ears of fish and record environmental changes that fish are exposed to throughout their lifes. Recent studies have shown that fish otoliths provide information on the accumulation of mineral and heavy metal in the environment. The accumulation of mineral and heavy metal in fish otoliths can be an important indicator for understanding environmental interactions and ultimately assessing the sustainability of fishery resources. In this study, 62 samples of Acanthobrama marmid, Alburnus mossulensis, Paracapoeta trutta, Capoeta umbla, Carassius gibelio, Chondrostoma regium, Cyprinion kais, Cyprinion macrostomum, Luciobarbus mystaceus and Planiliza abu were obtained from fishermen in the Tigris River. The presence of Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn were analysed by inductively couple plasma optical emission apectrometry (ICP-OES) in the otoliths. The average levels of heavy metals residues in the otoliths were determined as Co>Cr>Cu>Fe>Mn>Ni>Pb and Zn. The minerals Ca, K, Mg, Na and P were found to be statistically significant among fish species (P<0.05). According to Tukey HSD multiple comparison test, the highest values of Ca, K and Na were found in P. abu and Mg in C. gibelio. The data can be used as a reference for the evaluation of the accumulation of mineral and heavy metal in fish otoliths in terms of fishery management and environmental protection, and can be compared with the data from studies in different fisheries.